2018
DOI: 10.1002/jid.3358
|View full text |Cite
|
Sign up to set email alerts
|

Temporary and Permanent Effects of Remittances on Economic Growth in Ecuador

Abstract: This article analyses the temporary and permanent effects of remittances on subnational economic growth in Ecuador. We find that both effects are statistically significant. However, while the size of first is negligible, the magnitude of the permanent effect is inversely related to the stage of development. Copyright © 2018 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As the subjects of this kind of research (and, accordingly, the factors of influence) were identified: foreign direct investment (Rafat, 2018); the level of development of stock market institutions (Fufa & Kim, 2018); membership of countries in international economic integration associations (in particular, the TRANS-Pacific partner-ship (Khan et al, 2018) and the Association of Southeast Asian Nations (Karimi & Daiari, 2018)); the level of openness of national economies (Lee & Kim, 2018); the level of efficiency of natural resource potential and energy efficiency (Baloch et al, 2018); innovation, development of science and education (Batabyal & Yoo, 2018); demographic and urban processes (Ibrahiem, 2018;Cruz & Ahmed, 2018;Frick & Rodriguez-Pose, 2018); state fiscal policy (Esteve & Tamarit, 2018); the dynamics of the national currency and foreign remittances of individuals (Pontarollo & Mendieta Munoz, 2018); form of administrative-territorial structure and methods of regional management (Pink-Harper, 2018). We also note the significant interest of researchers in the processes of economic growth in developing countries, such as Liberia, Egypt, Pakistan, Vietnam, Ecuador and other Latin American countries (Khan et al, 2018;Roquez-Diaz & Escot, 2018;Baloch et al, 2018;Bunte et al, 2018;Ibrahiem, 2018;Maune, 2018;Nguyen & Pham, 2018;Pontarollo & Mendieta Munoz, 2018). Worth to be noted works that a devoted topost-socialist country of Eastern Europe, such as Slovakia, Slovenia, Poland, Lithuania, Czech Republic (Mahmood & Ahmad, 2018;Raisová, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…As the subjects of this kind of research (and, accordingly, the factors of influence) were identified: foreign direct investment (Rafat, 2018); the level of development of stock market institutions (Fufa & Kim, 2018); membership of countries in international economic integration associations (in particular, the TRANS-Pacific partner-ship (Khan et al, 2018) and the Association of Southeast Asian Nations (Karimi & Daiari, 2018)); the level of openness of national economies (Lee & Kim, 2018); the level of efficiency of natural resource potential and energy efficiency (Baloch et al, 2018); innovation, development of science and education (Batabyal & Yoo, 2018); demographic and urban processes (Ibrahiem, 2018;Cruz & Ahmed, 2018;Frick & Rodriguez-Pose, 2018); state fiscal policy (Esteve & Tamarit, 2018); the dynamics of the national currency and foreign remittances of individuals (Pontarollo & Mendieta Munoz, 2018); form of administrative-territorial structure and methods of regional management (Pink-Harper, 2018). We also note the significant interest of researchers in the processes of economic growth in developing countries, such as Liberia, Egypt, Pakistan, Vietnam, Ecuador and other Latin American countries (Khan et al, 2018;Roquez-Diaz & Escot, 2018;Baloch et al, 2018;Bunte et al, 2018;Ibrahiem, 2018;Maune, 2018;Nguyen & Pham, 2018;Pontarollo & Mendieta Munoz, 2018). Worth to be noted works that a devoted topost-socialist country of Eastern Europe, such as Slovakia, Slovenia, Poland, Lithuania, Czech Republic (Mahmood & Ahmad, 2018;Raisová, 2018).…”
Section: Methodsmentioning
confidence: 99%